2017
DOI: 10.1007/s00167-017-4528-4
|View full text |Cite
|
Sign up to set email alerts
|

ACL-reconstructed and ACL-deficient individuals show differentiated trunk, hip, and knee kinematics during vertical hops more than 20 years post-injury

Abstract: PurposeLittle is known regarding movement strategies in the long term following injury of the anterior cruciate ligament (ACL), and even less about comparisons of reconstructed and deficient knees in relation to healthy controls. The present purpose was to compare trunk, hip, and knee kinematics during a one-leg vertical hop (VH) ~20 years post-ACL injury between persons treated with surgery and physiotherapy (ACLR), solely physiotherapy (ACLPT), and controls (CTRL). Between-leg kinematic differences within gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 31 publications
6
45
1
Order By: Relevance
“…First, compensatory mechanisms can be acting to avoid knee rotation, regardless of the amount of rotation torque calculated by inverse dynamics. These compensations may include complex neuromuscular adaptations, which lead to multilevel protective strategies (20,21). Secondly, it is possible that the method used to collect and calculate knee rotation was not sensitive enough.…”
Section: Discussionmentioning
confidence: 99%
“…First, compensatory mechanisms can be acting to avoid knee rotation, regardless of the amount of rotation torque calculated by inverse dynamics. These compensations may include complex neuromuscular adaptations, which lead to multilevel protective strategies (20,21). Secondly, it is possible that the method used to collect and calculate knee rotation was not sensitive enough.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another question arises, namely, what the consequences of the altered between-limb symmetry during hop landing may be. Altered loadings of the knee joint may trigger the development of osteoarthritis and therefore influence quality of life [13,28]. Some authors also suggest that altered movement strategies in ACL-reconstructed patients are partially responsible for the high second-injury rates in this population [45].…”
Section: Discussionmentioning
confidence: 99%
“…The vertical hop is a multi-joint movement task that is commonly used in the clinical environment, and is considered an important dynamic movement in physical activity [13,14]. The current literature highlights the landing strategies analysis during standardized jump tasks as an interesting assessment tool, and several studies have reported an asymmetric landing pattern among patients after ACLR [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for a successful return post-injury to sports or leisure activities that place considerable load on the lower limb (and in particular the knee joint), individuals should demonstrate sufficient lower limb control during tasks that involve cutting and side-to-side manoeuvres. This requires tests that are specifically designed to evaluate landing mechanics during such conditions, both of the lower limb but also of the trunk due to interrelationship of joint motion (Markström, Tengman, & Häger, 2017;Shimokochi et al, 2013). However, no study to date have evaluated reliability and agreement of trunk, hip, and knee landing mechanics during such side-to-side tasks for ACLR persons.…”
Section: Introductionmentioning
confidence: 99%